2011
DOI: 10.1302/0301-620x.93b11.27632
|View full text |Cite
|
Sign up to set email alerts
|

Extra-articular techniques in anterior cruciate ligament reconstruction

Abstract: This annotation considers the place of extra-articular reconstruction in the treatment of anterior cruciate ligament (ACL) deficiency. Extra-articular reconstruction has been employed over the last century to address ACL deficiency. However, the technique has not gained favour, primarily due to residual instability and the subsequent development of degenerative changes in the lateral compartment of the knee. Thus intra-articular reconstruction has become the technique of choice. However, intra-articular recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 84 publications
3
106
0
4
Order By: Relevance
“…In addition, most extraarticular procedures described in the included trials are nonanatomic. As knowledge of the anterolateral compartment anatomy of the knee evolves, repair techniques of specific structures and more anatomic extraarticular reconstruction techniques may be developed, which may improve results and minimize donor site morbidity [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, most extraarticular procedures described in the included trials are nonanatomic. As knowledge of the anterolateral compartment anatomy of the knee evolves, repair techniques of specific structures and more anatomic extraarticular reconstruction techniques may be developed, which may improve results and minimize donor site morbidity [12].…”
Section: Discussionmentioning
confidence: 99%
“…Some ACL injuries may be more complex than previously believed, and a combination of central and peripheral structures appear to be involved in the pathoanatomy of pivot shift injury. Previous studies also have shown that the addition of an extraarticular lateral restraint can decrease rotational instability, as assessed by the pivot shift test [12,13,24]. Understanding the improved Lachman test results among patients who underwent combined ACL reconstruction is less straightforward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If at first, this anterolateral reconstruction gave quite good results, we soon noticed a clinical deterioration in outcome. This evolution was later confirmed by Dodds [19] who, in 2011, wrote: the technique (extra-articular reconstruction) has not gained favor due to the residual instability and the subsequent development of degenerative changes.…”
Section: 'Smentioning
confidence: 92%
“…The surgical technique used during ACL reconstruction varies widely not only from country to country but even within departments of the same hospital. Different techniques include arthroscopic vs open surgery, intra vs extra-articular reconstruction, femoral tunnel placement, number of graft strands, single vs double bundle and fixation method [16][17][18][19][20] . This heterogeneity of techniques makes comparison of graft choice difficult.…”
Section: Minireviewsmentioning
confidence: 99%